One-piece resection for the treatment of ventral intradural extramedullary spinal meningioma: a retrospective study - Guangqing Cao; Xinao Li; Dachuan Wang; Yachao Zhao (Frontiers in Oncology)
ObjectiveThis study aimed to evaluate the feasibility and efficacy of one-piece resection for the treatment of ventral intradural extramedullary spinal meningiomas (VIESMs).MethodsBetween January 2017 and December 2023, all patients who underwent one-piece resection for VIESMs were retrospectively reviewed with their demographic, intraoperative and postoperative data being recorded. In addition, postoperative neurological status based on the modified McCormick functional schema (mMFS), along with radiological manifestations on the magnetic resonance imaging (MRI) were assessed and compared with that before the operation.ResultsA total of 27 cases (7 men and 20 women) with an average age of 63.37 ± 10.48 years old were included in the present study with the operation time, blood loss, length of hospital stay, and follow-up periods being 292.41 ± 42.64 min, 286.85 ± 47.03 ml, 10.37 ± 1.69 days, and 16.81 ± 10.79 months, respectively. Postoperatively, one case experienced cerebrospinal fluid leakage without neurological deterioration. At the final follow-up, the mMFS scores were unchanged in seven (25.93%) cases while they improved in the remaining 20 (74.07%) cases. Finally, the MRI examinations showed that one-piece resection was successfully performed for each VIESM without a recurrence.ConclusionOne-piece resection was a feasible, safe and effective procedure for treating VIESMs. Partial removal of the ipsilateral pedicle, facet joint, and even posterior vertebral wall to establish a wide surgical corridor and vision, resection of the dentate ligaments to minimize spinal cord traction, and meticulous coagulation of the dural attachment to reduce recurrence were the key technical points.